Presence of mutans streptococci and Candida spp. in dental plaque/dentine of carious teeth and early childhood caries - de Carvalho, Fabiola Galbiatti; Silva, Danilo Souza; Hebling, Josimeri; Spolidório, Luis Carlos [UNESP]; Palomari Spolidorio, Denise Madalena (Elsevier B.V., 2006)
This study determined the presence of mutans streptococci and Candida spp. in supragingival. dental plaque and infected dentine of caries-free children, with early childhood caries and caries. Pooled samples of dental plaque and infected dentine were collected from 56 children aged 1-5 years, which were divided into 3 groups: early childhood caries (ECC); caries and caries-free. Infected dentine was collected in ECC and caries groups to compare the frequency of these microorganisms in the collected sites. The samples were inoculated in SB20 and SA medium, for mutans streptococci and Candida spp., respectively, and incubated at 37 degrees C for 48 h. Colony growth was verified and the identification was performed by biochemical tests and CHROMagar Candida. Fisher's test or chi-square (chi(2)) were applied (p = 0.05). The more prevalent species were S. mutans and Candida albicans in ECC (85.4% and 60.4%, respectively), independently of the sample site. S. mutans only was significantly associated with carious teeth, whether in early childhood caries or not. However, the frequency of C. albicans in ECC was higher when compared to caries and caries-free groups. There is a significant association between the presence of C. albicans and early childhood caries. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: early childhood caries; mutans streptococci; Candida albicans